Variabilitas Sea Surface Temperature (SST) di Wilayah Indonesia Akibat Pengaruh Musim - Dharlita Kusumaningdyah, Antiq; Djuniadi, Djuniadi; Hearttiana, Venny; AlFahmi, Furqon; Made Darma, Ngurah (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study analyzes the distribution pattern of sea surface temperature (SST) in Indonesia throughout the year and examines its impact on marine ecosystems and other marine parameters. SST in Indonesia shows significant seasonal variation, influenced by the apparent motion of the sun and seasonal wind circulation patterns. High SST during the rainy season supports convection and rainfall activities, but has the potential to increase the risk of coral bleaching. Conversely, low SST during the dry season triggers an upwelling phenomenon that brings nutrients from the bottom layer of the sea to the surface, increasing primary productivity. In addition, changes in SST affect salinity, ocean currents, and ocean wave intensity, which have important implications for marine ecosystems and marine resource management. These findings provide in-depth insights that are relevant to support climate change mitigation and adaptation planning to global climate dynamics.   Keywords: Sea Surface Temperature, Apparent Motion of the Sun, Marine Ecosystems, Seasonal Variability.